Neuroradiological Changes Following Single or Repetitive Mild TBI - Kulkarni, Praveen; Morrison, Thomas R.; Cai, Xuezhu; Iriah, Sade; Simon, Neal; Sabrick, Julia; Neuroth, Lucas; Ferris, Craig F. (Frontiers in Systems Neuroscience, 2019)
Objectives: To test the hypothesis that there are differences in neuroradiological measures between single and repeated mild TBI using multimodal MRI. Methods: A closed-head momentum exchange model was used to produce one or three mild head injuries in young adult male rats as compared to non-injured, age and weight-matched controls. Six-seven weeks post-injury, rats were studied for deficits in cognitive and motor function. Seven-eight weeks post-injury changes in brain anatomy and function were evaluated through analysis of high resolution T2 weighted images, resting state BOLD functional connectivity, and diffusion weighted imaging with quantitative anisotropy. Results: Head injuries occurred without skull fracture or signs of intracranial bleeding or contusion. There were no significant differences in cognitive or motors behaviors between experimental groups. With a single mild hit, the affected areas were limited to the caudate/putamen and central amygdala. Rats hit three times showed altered diffusivity in white matter tracts, basal ganglia, central amygdala, brainstem, and cerebellum. Comparing three hits to one hit showed a similar pattern of change underscoring a dose effect of repeated head injury on the brainstem and cerebellum. Disruption of functional connectivity was pronounced with three mild hits. The midbrain dopamine system, hippocampus, and brainstem/cerebellum showed hypoconnectivity. Interestingly, rats exposed to one hit showed enhanced functional connectivity (or hyperconnectivity) across brain sites, particularly between the olfactory system and the cerebellum. Interpretation: Neuroradiological evidence of altered brain structure and function, particularly in striatal and midbrain dopaminergic areas, persists long after mild repetitive head injury. These changes may serve as biomarkers of neurodegeneration and risk for dementia later in life.